An embedded tactile and force sensor for robotic manipulation and grasping - Cannata, G.; Maggiali, M. (5th IEEE-RAS International Conference on Humanoid Robots, 2005, 2005)
A new fully embedded tactile/force sensor system is presented. The sensor has been designed to be installed on a dextrous robot gripper (MAC-HAND). The tactile sensor consists of a matrix of 64 electrodes, etched on a flexible PCB covered by a conductive rubber layer. The force sensor is an off-the-shelf integrated three components micro-joystick. The analog and digital electronics is fully embedded with the sensor that is a self-standing module mounted on each finger phalange